Pericardial effusion predicts mortality in patients with chronic obstructive pulmonary disease - Can Yücel Karabay; Gokhan Gol; Arzu Kalayci; Alev Kilicgedik; Merve Ciftci; Hakan Gunen (KARE Publishing, 2015)
Objectives: Chronic obstructive pulmonary disease (COPD) is an increasingly important cause of morbidity and mortality worldwide. Pericardial effusion (PE) is a current issue proven to be a mortality predictor, especially in pulmonary arterial hypertension. In this study, we aimed to evaluate the prognostic value of PE in COPD. Study design: The study cohort consisted of 488 COPD patients and a control group of 50 healthy patients. At the start of the study, 37 patients (7.5%) had PE. Mean followup time was 12 months (range; 1-16 months). Clinical spirometric and echocardiographic data were compared between patients with PE(+) group (n=37), patients without PE(-) group (n=451) and the healthy control group. Results: Right ventricular functions were more depressed and pulmonary arterial pressure was more elevated in the PE(+) group. Also, Kaplan-Meier survival curve analysis showed that at one-year follow- up, mortality was higher in the PE(+) group: PE(-) group 139 (30.8%), PE(+) group 21 (56.8%) log-Rank p value: 0.009). Age, presence of PE, and oxygen usage were independent predictors of mortality in Cox regression analysis. Conclusion: Presence of PE predicts mortality in COPD patients at one-year follow-up.